Working with Soil: Craft, Design and Coactive Power - Latva-Somppi, Riikka (HannahArendt.net, 2022)
This report looks at three interdisciplinary craft and design projects by the Finland-based Working with Soil group that engages with ecological concerns in the context of local soils. The group co-operates with established institutes, such as environmental organisations, museums and universities. They invite other craft and design practitioners, artists, scientists, and the public to join them in exploring the relationality of humans and soil. While Arendt’s concepts of ‘labour’ and ‘work’ are attached to ideas of the earth and the world, the concept of ‘action’ is used in reflecting on the practical engagement with the environmental concerns. The processual elements of the projects are organized in exhibitions as ‘laboratories’ where ongoing work and events occur in the form of open studios and fieldwork as well as talks and other public events creating a ‘space of appearance’ to participate in the politics of sustainability. As such, these projects can be considered practical exercises of political thought.